Competition Dynamics of SME Plastics Industries in Bangladesh Using Triple Triangle Framework Model: An Assessment (International Journal of Scientific Research and Management (IJSRM), 2017)
Starting as a backward linkage industry, the plastics sector in Bangladesh is achieving a remarkable growth and expansion to become one of the most promising sectors contributing 1.20 per cent of the country’s GDP with a total investment of Tk 185.5 billion holding a market share of only 0.01% against the global demands of 590 billion with the ranking of 89 in world exports. Out of available 5,000 plastic industries almost 98 percent belongs to SME. Despite having remarkable achievement with almost 500% growth in export over the past twelve years, Bangladesh plastics industry has been suffering from lack of strategic planned direction towards achieving long-term sustainable inclusive growth. In this study, a thorough analysis of the relevant issues using Triple Triangle Framework (TTF) model helped to understand the competition dynamics of the Bangladesh SME Plastic Industry through the identification of challenges and opportunities relevant to the sector.